Privatization Experiences in France - Michel Berne; Gérard Pogorel (Center for Economic Studies and ifo Institute (CESifo), 2004)
France lived through a long period of nationalization until the early 1980s, when nearly all the largest industrials firms as well as all the banks and public services were state-owned. Since then, a series of privatization moves have caused the state sector to shrink. Public services present a complex situation. For example, after its IPO, the national telecommunications operator France Telecom was simultaneously subjected to the deregulation of the telecom market in the world and to a new type of governance. EDF, the national electricity producer is next in line and should experience the same problems and opportunities.
Keywords: 330; privatisation; competition; regulation; utilities